High-Throughput Screening of Formulations to Optimize the Thermal Stability of a Therapeutic Monoclonal Antibody. (April 2015) - Niedziela-Majka, Anita; Kan, Elaine; Weissburg, Perry; Mehra, Upasana; Sellers, Scott; Sakowicz, Roman
Monoclonal antibodies (mAbs) are an important class of biotherapeutics. Successful development of a mAb depends not only on its biological activity but also on its physicochemical properties, such as homogeneity and stability. mAb stability is affected by its formulation. Among the many techniques used to study the stability of mAbs, differential scanning fluorimetry (DSF) offers both excellent throughput and minimal material consumption. DSF measures the temperature of the protein unfolding transition (Tm ) based on the change in fluorescence intensity of the environmentally sensitive dye SYPRO Orange. With DSF adapted to a 96-well plate format, we have shown that low-pH or high-salt concentrations decrease the thermal stability of mAb1, whereas some excipients, such as sucrose, polysorbate 80, and sodium phosphate, increase its stability. The basal fluorescence of SYPRO Orange was enhanced by the presence of detergents, limiting the use of this approach to diluted detergent solutions. Throughput of DSF can be increased further with the use of a 384-well plate. DSF thermograms are in good agreement with the melting profiles obtained by differential scanning calorimetry (DSC). The Tm s determined by DSF and DSC were well correlated, with the former being on average lower by 3 °C.